Proceedings of the Seventh Annual ACM/IEEE International Conference on Human-Robot Interaction 2012
DOI: 10.1145/2157689.2157818
|View full text |Cite
|
Sign up to set email alerts
|

Human-swarm interaction through distributed cooperative gesture recognition

Abstract: VIDEO OVERVIEWThe video presents the first results of a Swiss-funded project focusing on symbiotic peer-to-peer interaction and cooperation between humans and robot swarms. As a first step, we considered human-swarm interaction, and selected the use of hand gestures to let a human communicate with a swarm of relatively simple mobile robots. In our scenario, a hand gesture encodes a command, that the swarm will execute. The robots that we used are the foot-bots, developed in the Swarmanoid project [1].Hand gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…Most of the research on proximal swarm interactions has focused on enabling the interaction through gesture recognition [88]- [90] as well as face engagement and speech [91]. The distributed gesture recognition presented in [88] and [90] facilitates the communication of a wide range of instructions to all swarm robots within sight.…”
Section: B Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research on proximal swarm interactions has focused on enabling the interaction through gesture recognition [88]- [90] as well as face engagement and speech [91]. The distributed gesture recognition presented in [88] and [90] facilitates the communication of a wide range of instructions to all swarm robots within sight.…”
Section: B Communicationmentioning
confidence: 99%
“…The distributed gesture recognition presented in [88] and [90] facilitates the communication of a wide range of instructions to all swarm robots within sight. The human wears an orange glove that is easily recognizable by the cameras on board the robots.…”
Section: B Communicationmentioning
confidence: 99%
“…This has been done for a single robot system (e.g. [12], [34]); however, an interesting extension would be to coordinate multiple robots to cooperatively estimate the vector given the system's ability to simultaneously capture images of the user from multiple angles (in the spirit of [13]). …”
Section: Discussionmentioning
confidence: 99%
“…Earlier work by Kortenkamp et al presents a mobile robot that uses an active vision system to recognize static gestures by building a skeleton model of the human operator; a vector of the human's arm is used to direct the robot to a particular point [12]. Giusti et al [13] demonstrated how a swarm of mobile robots can cooperatively detect a static human gesture and act upon it.…”
Section: A Uninstrumented Human Robot Interactionmentioning
confidence: 99%
“…To the best of our knowledge, there is only one existing HSI approach that does not rely on an extra modelling layer: Giusti et al's [9] hand gesture-based interaction system. The goal of their work is to allow robots to decode hand gestures.…”
Section: Related Workmentioning
confidence: 99%